PENGARUH HARGA, PRODUK, PROMOSI, DAN SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN PADA PT. YAKULT INDONESIA PERSADA CABANG PEKANBARU - Julista Nainggolan; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Price is amount of money imposed on product or service. Definite of price extensivelyis amount of value exchanged by consumer for ownershipbenefits or use of a product or service. Product in the form of tangible goods or not including warp, color, price,prestige of company and retailer, company service. Promotion is activities performed to communicate the goodness of the product. Distribution channel is one very important function in marketing for develop and smooth the flow product and service start from producer until to consumer according to the amount needed. Sales volume is the amount of sales result obtained by the company with make a payment to process transfer of goods from one ofbusiness entity or an individual to other part.This research was conducted at PT Yakult Indonesia Persada cabang Pekanbaru. As for the purpose of this research is to know influence of price, product, promotion, and distribution channel on sales volume at PT. Yakult Indonesia Persada cabang Pekanbaru. Price, product, promotion, and distribution channel as the independent variable (X1X2 X3X4) meanwhile sales volume as the dependent variable (Y). Internal problems of this research is sales volume of the otlet PT Yakult Indonesia Persada cabang Pekanbaru who experienced fluctuations and tends to decrease every year, even not reach sales target. Seen from presentation of yakult product sales realization in the last 5 years. Sample of this reseach taken as 94 respondents of the calculated population using Slovin formula. Data obtained from the result of questionnaire then processed to be examined with statistic through SPSS. From the result of study what is done shows that price, product, promotion, and distribution channel influence positive and significant to sales volume at PT. Yakult Indonesia Persada Cabang Pekanbaru.Keywords: Price, Product, Promotion, and Distribution Channel, On Sales